Internalisasi Kultur Pesantren pada Pembentukan Karakter Siswa Melalui Desain Berbasis Kelas dan Organisasi Sekolah - Syamsul Arifin; Mega Silvia (Bidayatuna, 2020)
Globalization poses strong and diverse challenges, one of which is the rampant moral degradation that still often occurs everywhere, including at the school level, for that it is necessary to instill and develop values ​​in students. Pesantren is considered capable of being a medium for scientific transformation that can shape good character through its strong characteristics and culture. In building the character of students, it is not only done in classroom learning, but can be done through the development of other activities in school. This research uses descriptive qualitative method, with a case study approach. Data collection techniques using interviews, observation and documentation which were analyzed descriptively. While the data analysis used was data reduction, data presentation and conclusion drawing. The validity of the data used three techniques, namely extension of participation, persistence of observation and triangulation. This research shows that; the application of internalizing pesantren culture to character building students includes class-based design, school culture-based design and organization-based design. The factors supporting and inhibiting the internalization of pesantren culture on the formation of student character are seen from the students themselves, the carrying capacity of all school members and infrastructure.